2020
DOI: 10.37018/krcw7511
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome of manipulation under anaesthesia for the treatment of frozen shoulder

Abstract: Background: Frozen shoulder is defined as painful progressive loss of shoulder movements with unknown etiology. It is a self-limiting disease with the natural history of 18-30 months but with residual pain and restriction of shoulder movement. Its incidence is 2-5%. Various treatment modalities include benign neglect, physical therapy, non-steroidal anti-inflammatory medications, oral glucocorticoids, distention arthrography, intra articular steroid injections, closed manipulation under anaesthesia (MUA) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…In line with our results Arshad et al [18] found out that the therapeutic outcomes of 20% topical ZnO of cutaneous warts of hands and feet, 49.8% patients had CR at the termination of three months of therapy [6] .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with our results Arshad et al [18] found out that the therapeutic outcomes of 20% topical ZnO of cutaneous warts of hands and feet, 49.8% patients had CR at the termination of three months of therapy [6] .…”
Section: Discussionsupporting
confidence: 92%
“…Topical Zn could trigger a sequence of immunological occasions. It has the ability to induce inflammation with subsequent activation of Tlymphocytes, which ultimately ends in INF discharge, as a result leading to action of macrophages against wart-derived keratinocytes [18] . ILI of PRP in plantar warts could be efficient and safe immunotherapy; this could be clarified by the fact that PLT express a lot of TLRs 1, 2, 3, 4, 6, 7, and 9 [19] .…”
Section: Discussionmentioning
confidence: 99%